Analisis Pengaruh Pekerja Migran Perempuan, Tingkat Pendidikan, Dan Remitansi Terhadap Pendapatan Keluarga (Studi Kasus Desa Bandar Agung, Lampung Timur) - Rizky Rafliansyah; Toto Gunarto; Muhiddin Sirat; Emi Maimunah; Zulfa Emalia (BULLET : Jurnal Multidisiplin Ilmu, 2022)
This study aims to analyze the effect of female migrant workers, education level, and remittances on family income (Case Study in Bandar Agung Village, Bandar Sribhawono District, East Lampung Regency). The data used in this study is primary data originating from Bandar Agung Village which is supported by secondary data obtained from the publication of BPS Indonesia, the Indonesian Migrant Workers Protection Agency (BP2MI). The data used in this research is in the form of cross section data. The method used in this study is multiple linear regression using SPSS 21 as a statistical estimation tool. The results showed that together the variables of female migrant workers, education level, and remittances had a significant effect on family income